2020
DOI: 10.1080/17476348.2021.1853529
|View full text |Cite
|
Sign up to set email alerts
|

Management of COVID-19 from the pulmonologist’s perspective: a narrative review

Abstract: Introduction: The COVID-19 pandemic has provided global challenges to healthcare facilities in ensuring delivery of care to patients. Tremendous international collaboration has enabled swift formulation of evidence-based guidelines that aim to clarify day-today issues faced by physicians and other healthcare providers on the frontlines. Areas Covered: In order to provide answers to the common questions and dilemmas faced by physicians and policy makers, especially those handling pulmonary manifestations of COV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 65 publications
0
7
0
1
Order By: Relevance
“…All of them had severe COVID‐19 illness, with six patients (60%) being admitted in intensive care unit and four (40%) patients in general ward. All of them had received steroids for COVID‐19 illness in variable doses and durations, as per local guidelines 5 . During the present hospitalisation, eight (80%) patients presented with cough as the predominant complaint, shortness of breath was present in five (50%) and haemoptysis was seen in four (40%) of them.…”
Section: Resultsmentioning
confidence: 95%
“…All of them had severe COVID‐19 illness, with six patients (60%) being admitted in intensive care unit and four (40%) patients in general ward. All of them had received steroids for COVID‐19 illness in variable doses and durations, as per local guidelines 5 . During the present hospitalisation, eight (80%) patients presented with cough as the predominant complaint, shortness of breath was present in five (50%) and haemoptysis was seen in four (40%) of them.…”
Section: Resultsmentioning
confidence: 95%
“…The diverse subjective viewpoints of the public as well as the objective viewpoints of science both need to be taken into account in order to obtain workable solutions for the common good. A careful consideration of the consequences of specific options for specific age groups and medical comorbidities also being required. Specialists from internal medicine like pulmonologists (Kumar et al 2020 28 ), together with radiologists (Huang et al 2020 29 ), showed very early the morphological features of lung affection by the virus. Pulmonology also showed long‐term consequences of COVID‐19 (LongCovid) by means of functional diagnostics and radiology imaging (Greenhalgh et al 2020 30 ).…”
Section: Brief Timeline Of Engagement Of Medical Disciplines and Thei...mentioning
confidence: 99%
“…COVID-19 is caused by the SARS-CoV-2 virus, and respiratory system is the most commonly involved organ system in COVID-19. 1 The respiratory manifestations of COVID-19 range from mild upper respiratory symptoms to life-threatening severe acute respiratory distress syndrome (ARDS) requiring invasive mechanical ventilatory support. CT of the chest shows typically bilateral ground-glass opacities predominantly in the lower lobes, mainly in a peripheral and subpleural location.…”
Section: Introductionmentioning
confidence: 99%